Virtual reality-assisted language learning: A follow-up review (2018–2022) - Hua, Congchao; Wang, Jia (Frontiers in Psychology, 2023)
Virtual reality (VR) is considered an “emerging technology in language education” in Parmaxi (2020, p. 1), which reviews 26 articles on VR-assisted language learning (VRALL) published between 2015 and 2018. VR technology has been developing rapidly and receiving much more attention in language learning especially in the post-pandemic era. Therefore, following up Parmaxi (2020), this paper tracks the new trends of VRALL by reviewing 38 empirical studies published between 2018 and 2022. The main findings are: 1) the scope of research on VRALL has expanded in terms of number of studies, type of participants, research focus, language and language skill, and type of VR technology investigated; 2) more cognitive and affective benefits as well as drawbacks of VRALL have been reported than before. Implications are drawn for practitioners and researchers in the field of VRALL.